Going concern: estimation algorithm - Kzykeyeva, A. S. (Journal of Economic Research & Business Administration, 2016)
In a market economy becomes essential accuracy of the financial statements. Potential investors, buyers, lenders want to be sure that the company will continue to exist, they would not violate the conditions of contracts and the financial statements reflect all the warning signs of any crisis and threat. In this connection special importance accepts the principle of going concern. The article deals with the current problems with the assessment of going concern, affecting the accuracy of the financial statements. Specific criteria were developed to assess the activities of the company in the long term. The concrete algorithm that makes it possible through the implementation of concrete steps to assess compliance with the principle of going concern. The article also lists certain types of audit documents to be used in assessing the position of the company in terms of the going concern assumption.